Decoding MUC1 and AR axis in a radiation-induced neuroendocrine prostate cancer cell-subpopulation unveils novel therapeutic targets - Catarina Macedo-Silva; Ângela Albuquerque-Castro; Iris Carriço; Joana Lencart; Isa Carneiro; Lucia Altucci; João Lobo; Vera Miranda-Gonçalves; Rui Henrique; Margareta P. Correia; Carmen Jerónimo (Cell Death Discovery)
Abstract Despite the initial efficacy of radiotherapy (RT) in treating prostate adenocarcinoma (PCa), disease progression can lead to the emergence of neuroendocrine prostate cancer (NEPC) - a highly aggressive malignancy for which standard therapies are mostly ineffective. Although oncogenic MUC1-C is a leading driver of NEPC and of PCa lineage plasticity, its putative role in response to RT, including RT-induced neuroendocrine transdifferentiation (tNED), has not been explored. We thus aimed to explore the interplay between androgen receptor (AR) signaling and MUC1 in PCa progression to NEPC. Firstly, using a radioresistant PCa cell line (22Rv1-RR), we demonstrated that epigenetic suppression of AR signaling led to MUC1/MUC1-C upregulation, which seems to be activated through γSTAT3. MUC1 activation is positively associated with increased expression of neuroendocrine-related markers, including CD56, chromogranin A, synaptophysin, and INSM transcriptional repressor 1 (INSM1). In NEPC tissues and compared to prostate adenocarcinoma, MUC1 was upregulated and negatively correlated with AR, which was suppressed. Finally, proteomic analyses revealed that MUC1 activation upon RT selective pressure led to the acquisition of stemness features, induction of epithelial to mesenchymal transition, and enhancement of basal cell-like traits. Notably, MUC1 knockdown significantly boosted response to RT in both 22Rv1-RR and DU145 cell lines. Moreover, AR-induced overexpression in PC3 cell lines entailed MUC1 downregulation, resulting in attenuated neuroendocrine traits and radioresistance, as well as impaired cell migration and invasion capabilities. Collectively, these results highlight MUC1 as a promising radiosensitization target and may ultimately help overcome therapy resistance and NEPC progression.